Pediatric medical emergencies - Dietrich, Ann M. (New York : Oxford University Press, 2020)
Let's face it sick children can be very frightening! Volume I of this two volume series in the What Do I do Now series focuses on pediatric medical emergencies. Through case studies the book targets challenging presentations and diagnostic approaches to help care for your youngest patients. Not sure how to approach a 5 week old with fever? A infant with a'blue spell'? A child with vomiting or abdominal pain? This book guides critical decision making through each scenario to give the skills needed to give the best care for pediatric patients.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 27, 2020).
Keywords: Pediatric emergencies